Novel Peptides Targeting the β-Clamp Rapidly Kill Planktonic and Biofilm Staphylococcus epidermidis Both in vitro and in vivo - Raeder, Synnøve Brandt; Sandbakken, Erik Thorvaldsen; Nepal, Anala; Løseth, Kirsti; Bergh, Kåre; Witsø, Eivind; Otterlei, Marit (Frontiers in Microbiology, 2021)
Antimicrobial resistance is an increasing threat to global health and challenges the way we treat infections. Peptides containing the PCNA interacting motif APIM (APIM-peptide) were recently shown to bind to the bacterial PCNA homolog, the beta (b)-clamp, and to have both antibacterial and anti-mutagenic activities. Here we explore the antibacterial effects of these peptides on Staphylococcus epidermidis, a bacterial species gaining increasing drug resistance which leads to difficult-to-treat chronic prosthetic joint infection (PJI). We show that APIM-peptides have a rapid bactericidal effect which when used at sublethal levels also increase the efficacy of gentamicin. In addition, APIM-peptides reduce development and eliminate already existing S. epidermidis biofilm. To study the potential use of APIM-peptides to avoid PJI, we used an in vivo bone graft model in rats where cement was added APIM-peptide, gentamicin, or a combination of these. The bone grafts containing cement with the combination contained significantly fewer bacteria than gentamicin only containing cement, which is the current standard of care. In summary, these results suggest that APIM-peptides can be a promising new drug candidate for anti-infective implant materials to use in the fight against resistant bacteria and chronic PJI.